Svalbard’s 2024 record summer: An early view of Arctic glacier meltdown? - Thomas Vikhamar Schuler; Rasmus Emil Benestad; Ketil Isaksen; Halfdan Pascal Kierulf; Jack Kohler; Geir Moholdt; Louise Steffensen Schmidt (Proceedings of the National Academy of Sciences, 2025)
A record-breaking melt season affected the Arctic glaciers of Svalbard in summer 2024 by a substantial margin. Across the entire archipelago, glacier melting corresponded to an anomaly of up to four SD and exceeded any previous observation. The pan-Svalbard mass loss in summer 2024 amounts to ~61.7 ± 11.1 Gt and corresponds to 1% of the total ice volume on Svalbard and is comparable to that of the Greenland ice sheet (55 ± 35 Gt), which occupies an area about 50 times larger. Altogether, Svalbard and other glacier regions surrounding the Barents Sea lost 102.1 ± 22.9 Gt of ice in a single year and contributed 0.27 ± 0.06 mm (of which 0.16 mm alone is due to Svalbard) to global sea-level, putting the circum-Barents region among the strongest contributors to global sea-level rise in 2024. Most of the 2024 glacier melt occurred during a 6-wk period of persistent atmospheric circulation pattern causing record-high air temperatures, an event with an extremely low recurrence interval under current climate conditions. However, future climate projections suggest that such temperature levels will become increasingly commonplace by the end of the 21st century, potentially even surpassing those of 2024. Svalbard’s summer of 2024 serves as a forecast for future glacier meltdown in the Arctic, offering a glimpse into conditions 70 y ahead.